Konstelasi Politik Pasca Perang Ngali di Bima - Sukarddin Sukarddin; Mulyati Mulyati; Faujiah Faujiah (Yupa: Historical Studies Journal, 2020)
Sultanate of Bima faces various challenges, especially in the economic and political fields of government. Trade freedom had been the main pillar of the economy, threatened by the Dutch trade monopoly. Sovereignty and territorial integrity are threatened by the " Lange Contract " ( long contract ) which was imposed by the Dutch colonial government . The agreement " Lange Contract " ( long contract ) with the Netherlands has made people's anger overflowed. Anger was manifested by the resistance of the people of N g Ali against occupation of the Netherlands in the years 1908-1909. The purpose of writing this is to examine more deeply about the background behind the constellation of politics in the Sultanate of Bima so that the P groaned Ngali , and the impact of P groaned Ngali.